Comparison of Outcome Measures in a US Birth Cohort Against Those in the National Maternity and Perinatal Audit Report [09O]. (May 2020) - Souter, Vivienne; Painter, Ian; Nethery, Elizabeth; Sitcov, Kristin
Abstract : INTRODUCTION: The aim of this study was to compare outcome measures in a US birth cohort against those reported in the 2019 National Maternity and Perinatal Audit (NMPA) Clinical Report. METHODS: This retrospective cohort study evaluated outcome measures for hospital births between 04/01/2016 and 03/31/2017 in a multicenter perinatal quality collaborative (OB COAP) based in the Northwest US, and compared them to rates in Great Britain's 2019 publically available NMPA Clinical Report. Outcome measures included mode of delivery, episiotomy, low Apgar (<7 at 5 minutes), 3rd/4th degree laceration, vaginal birth after cesarean (one previous cesarean only), and neonatal unit admission, for term singleton births, and neonatal unit admission for late preterm births (34+0–36+6 weeks). RESULTS: A total of 27, 267 births were included in the OB COAP cohort. Compared to unadjusted aggregate rates in the NMPA report, OB COAP had higher rates of cesarean birth (29.3% versus 25.7%), spontaneous vaginal birth (65.9% versus 61.6%), and neonatal unit admission (7.0% versus 5.8%) in term births, and neonatal unit admission in late preterm births (50.3% versus 41.9%). OB COAP had lower rates of operative vaginal birth (4.8% versus 12.5%), vaginal birth after cesarean (14.6% versus 24.5%), and episiotomy (3.1% versus 21.9%). The rate of 3rd/4th degree lacerations was slightly lower in OB COAP (2.8% versus 3.5%) and low Apgar rates were similar (1.3% in OB COAP and 1.2% in NMPA). CONCLUSION: Striking differences in outcome measures between the US cohort and rates in the NMPA Clinical Report, highlight potential strategies for quality improvement.